Hypoxia-induced neutrophil survival is mediated by HIF-1α–dependent NF-κB activity - Walmsley, Sarah R. (The Rockefeller University Press, 2005)
Neutrophils are key effector cells of the innate immune response and are required to migrate and function within adverse microenvironmental conditions. These inflammatory sites are characterized by low levels of oxygen and glucose and high levels of reductive metabolites. A major regulator of neutrophil functional longevity is the ability of these cells to undergo apoptosis. We examined the mechanism by which hypoxia causes an inhibition of neutrophil apoptosis in human and murine neutrophils. We show that neutrophils possess the hypoxia-inducible factor (HIF)-1α and factor inhibiting HIF (FIH) hydroxylase oxygen-sensing pathway and using HIF-1α–deficient myeloid cells demonstrate that HIF-1α is directly involved in regulating neutrophil survival in hypoxia. Gene array, TaqMan PCR, Western blotting, and oligonucleotide binding assays identify NF-κB as a novel hypoxia-regulated and HIF-dependent target, with inhibition of NF-κB by gliotoxin or parthenolide resulting in the abrogation of hypoxic survival. In addition, we identify macrophage inflammatory protein-1β as a novel hypoxia-induced neutrophil survival factor.